Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow

Engineering reactors for catalytic reactions - Ranade, Vivek V. (Journal of Chemical Sciences, 2014)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst which provides an alternative route of reaction with lower activation energy and better control on selectivity can make substantial impact on process viability and economics. Extensive studies have been conducted to establish sound basis for design and engineering of reactors for practising such catalytic reactions and for realizing improvements in reactor performance. In this article, application of recent (and not so recent) developments in engineering reactors for catalytic reactions is discussed. Some examples where performance enhancement was realized by catalyst design, appropriate choice of reactor, better injection and dispersion strategies and recent advances in process intensification/ multifunctional reactors are discussed to illustrate the approach.
Keywords: Catalyst; effectiveness; engineering; hydrodynamics; reactors

Electrical resistance tomography for gas holdup in a gas-liquid stirred tank reactor - Sardeshpande, Madhavi V.; Gupta, Suraj; Ranade, Vivek V. (Chemical Engineering Science, 2017)
Gas-Liquid flows in stirred tank reactors (STR) are used in many significant industrial operations such as hydrogenation, absorption, stripping, oxidation, hydrogenation, ozonation, chlorination, fermentation, etc. Gas-Liquid STRs are expected to perform several functions such as mixing, dispersing gas into liquid, mass and heat transfer and reactions. Gas hold up distribution and various flow regimes are the key parameters affecting performance of gas-liquid STRs. Various techniques such as visual analysis, photography, light attenuation, optical probe method are used to understand gas hold-up distribution within stirred tanks. Most of these techniques have some limitations with respect to measurement of gas hold up distribution. Electrical Resistance Tomography (ERT) is an upcoming technique for obtaining both qualitative and quantitative data on multiphase process units non-invasively and non-intrusively. In this work, an attempt was made to establish and validate the ERT technique for characterizing gas-liquid flows in a laboratory scale STR using the Rushton turbine impeller. ERT was used to study gas holdup and to identify flow regimes. The results were compared with the visual measurements as well as previously published correlations. The effect of gas flow rate, impeller speed on the mean gas holdup is discussed. The methodology and results presented in this work will be useful to effectively apply ERT for characterizing gas-liquid flows in stirred tanks. (C) 2017 Elsevier Ltd. All rights reserved.